Pengaruh Edukasi Dan Simulasi Dagusibu Obat Terhadap Peningkatan Keluarga Sadar Obat Di Desa Kedungbanteng Banyumas - Suryoputri, Masita Wulandari; Sunarto, Ade Martinus (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2019)
Education and simulation to dagusibu of drug is one of effort to prevent unwanted result of using drug, this includes increasing knowledge and awareness of the residents of kedungbanteng village related to the using and storing drugs. Education method that we used was active and participatory learning, this explains how to use and manage drug in proper ways (Dagusibu of drug), application through simulation or demonstration in how to manage properly, and also by evaluation through pretest and post-test. This activity is aimed for PKK candidate and residents Kedungbanteng, Kedungbanteng region, Banyumas regency. Based on the results of the pretest and posttest evaluation showed an increase in knowledge after being given education in the form of counseling, namely the number of respondents who received good grades (80-100) increased from 1 respondent (2.5%) to 12 respondents (30%). Monitoring results home visite also shows the existence of respondents who apply the method of using and managing drugs well and correctly, one of which is by storing drugs in a medicine box. Based on that shows education of Dagusibu and simulation of drug for drug management may increase people's knowledge in order to raise people's wealthness and family awareness of drug